Hubungan Pola Asuh Orang Tua dan Pemberian Stimulus Alat Permainan Edukatif (APE) Terhadap Perkembangan Motorik Halus Anak di PAUD Kelurahan Sendangguwo - witri Siti Nurhayati Sabatini Kusuma Dewi, Witri Hastuti (Sekolah Tinggi Ilmu Kesehatan (STIKes) Karya Husada Semarang, 2016)
Berdasarkan data WHO di Indonesia pada tahun 2012 jumlah anak yang diberikan permainan edukatif pada tahun 2010 mencapai hingga 24.120 jiwa dan pada tahun 2011 mencapai 25.100 jiwa. Cakupan deteksi dini tumbuh kembang anak balita tingkat Provinsi Jawa Tengah pada tahun 2012 sebesar 35,66%, hal ini Jauh di bawah target yang ditetapkan yaitu 90%. Mendeskripsikan hubungan pola asuh orang tua dan pemberian stimulus APE terhadap perkembangan motorik halus anak usia 3-5tahun di PAUD wilayah kelurahan Sendangguwo Semarang. Metode penelitian ini menggunakan penelitian kuantitatif dengan pendekatan analitik korelasi. Pengumpulan data dilakukan sendiri oleh peneliti dan data yang diperoleh dianalisa secara univariat dan bivariat dengan menggunakan uji chi-square dengan hasil penelitian yang menunjukkan (p= 0.000 dan p= 0.000 dengan α= 0,05). Ada hubungan pola asuh orang tua dan pemberian stimulus APE terhadap perkembangan motorik halus anak usia 3-5 tahun di PAUD wilayah kelurahan Sendangguwo Semarang.THE RELATIONSHIP OF PARENTING STYLE AND THE PROVIDING OF EDUCATIONAL TOYS (APE) WITH THE FINE MOTORIC DEVELOPMENT CHILDREN IN SENDANGGUWO AbstractBased on data from the in Indonesia in 2012 the number of children who are given educational toys on in 2010 amounted to 24 120 inhabitants and in 2011 reached 25,100 people. The stimulation toys on children is very helpful in the development of the child from an early age, with the knowledge of good parents, then the need for child development will be fulfilled Sixteen percent of toddlers Indonesia impaired growth, good development of fine and gross motor, hearing loss, less intelligence and delays , Coverage of early detection of growth and development of children under five levels of Central Java province in 2012 amounted to 35.66%, it is drastically below the set target of 90%. The purpose of this research was to describe the relationship of parenting style and the providing of educational toys (APE) with the fine motoric development of 3-5 years old children at early childhood education in sendangguwo semarang. This study was a quantitative study of correlation analytic approach. Collection of the data was done by the researcher and the data obtained were analyzed using univariate and bivariate using chi-square test with the results of studies showing (p= 0.000 and p= 0,000 with α= 0,05). Based on the results of research and discussion can be concluded that there is a relationship of parenting style and the providing of educational toys (APE) with the fine motoric development of 3-5 years old children at early childhood education in sendangguwo semarang. Keywords ;Parenting, The giving of Stimulus Educational Toys , finemotorics